Principled Exclusion: A Revised Approach to Article1(F)(a) of the Refugee Convention - Bond, Jennifer (2013)
The focus of this contribution is Article 1(F)(a), a section of the exclusion clause that has increased in both use and profile in recent years. Article 1(F)(a) applies to individuals who may be implicated in crimes against peace (more commonly known today as crimes of aggression), war crimes, or crimes against humanity as such crimes are defined in relevant international instruments. Where a decision maker finds that “there are serious reasons for considering that” an asylum seeker has committed one of these acts, the remainder of the Refugee Convention does not apply, and any protections to which the claimant would otherwise be entitled are consequently unavailable. Article 1(F)(a) is a particularly important part of the exclusion clause because it applies to those who have committed acts so wrongful that the international community has agreed to standards of universal applicability. It is a provision committed to ensuring that perpetrators of the worst international crimes do not subsequently benefit from the robust international protections available to refugees. The 2013 Michigan Colloquium on Challenges in International Refugee Law brought together experts committed to articulating a principled approach to exclusion under Article 1(F)(a). This paper was drafted as the background study for that meeting and was designed to provide general principles for study and debate. In particular, the paper calls for a revised paradigm for determining when an asylum seeker ought to be denied protection on the basis that he or she is individually responsible for the international crimes listed in Article 1(F)(a)